Observance of the Adherence to Antibiotic Prescriptions by Iraqi Dental Patients: A Different Perspective on Antimicrobial Resistance - Mohammed Khamas Hatem; Maryam Hameed Alwan (ILUNI MKK FKUI and PRODI MKK FKUI, 2025)
Background: The excessive use and abuse of antibiotics contribute to bacterial resistance, raising the risk of complications and treatment failures. This study investigates adherence to antibiotic prescriptions among Iraqi dental patients, highlighting implications for antimicrobial resistance.Objective: To assess adherence levels and identify factors influencing antibiotic therapy compliance among dental patients.Methods: A cross-sectional survey was conducted in which adult dental patients aged 18 and older, who had been prescribed antibiotics within the past year, participated. The modified Morisky Medication Adherence Scale-8 items was used to evaluate adherence, and data were analyzed with IBM SPSS Statistics software V26.Results: Among 100 participants, 56% reported forgetting to take their antibiotics, 45% intentionally skipped doses, and 53% reduced or halted their doses. Adherence levels were categorized as medium in 45%, low in 28%, and complete in 27%. There were no significant differences by gender; however, adherence varied significantly across age groups, being higher in those aged 39-59.Conclusion: The study underscores the need for targeted interventions to improve adherence to antibiotic therapy among dental patients, which is essential for mitigating antimicrobial resistance and enhancing treatment outcomes.